Lives on hold: the experiences of asylum seekers in Moria refugee camp - Moreira, Ana Luísa (2021)
Of the hundreds of thousands of people that formed the huge migratory flow of the so-called ‘refugee crisis’, many are currently living in refugee camps, at times without basic conditions. This research aims to describe the lived experience of these people and amplify their voices. In order to pursue this goal, we conducted 15 semi-structured interviews with asylum seekers accomodated in the Kara Tepe refugee camp but who had also had experience of life in Moria refugee camp (both camps are in Greece). We complemented these data with participant observations carried out in the Kara Tepe refugee camp and some visits at the surroundings of Moria camp. Our results highlight a much worse experience of asylum seekers in Moria refugee camp if compared to asylum seekers’ experience in Kara Tepe, with reports of overcrowding, hunger, lack of hygiene, poor healthcare, insecurity and violence. The psychological impact of the high number of adversities affecting people living under these circunstances also stood out, with evidence of distress experienced. We conclude by discussing the implications of our findings in terms of policy change.